Challenges to access and provision of palliative care for people who are homeless: a systematic review of qualitative research. Issue 1 (December 2016) - Hudson, Briony; Flemming, Kate; Shulman, Caroline; Candy, Bridget
Abstract Background People who are homeless or vulnerably housed are a marginalized group who often experience high rates of morbidity and die young as a result of complex problems. Access to health care and support can be challenging, with access to palliative care even more so. This review presents a synthesis of published qualitative research exploring from the perspective of homeless people and those working to support them, current challenges to palliative care access and provision, in addition to suggestions for what may improve palliative care for this population. Methods Systematic review of qualitative research analysed using thematic synthesis. PsycINFO, Medline, Sociological Abstracts, Social Services Abstracts, Science citations index and CINAHL were searched up to September 2016. Thematic synthesis involved a three-step inductive process to develop a deeper understanding of the challenges to and suggestions for the access and provision of palliative care for homeless people. Results Thirteen qualitative articles, reporting nine studies were identified. The challenges to access and provision to palliative care were drawn from the data covering three broad areas, namely "the chaotic lifestyles sometimes associated with being homeless", "the delivery of palliative care within a hostel for homeless people" and provision within "mainstream health care systems". Obstacles were related to homeless persons competing day-to-day priorities, their experience of stigma in mainstream settings, the high burden on hostel staff in supporting residents at the end of life and inflexibility in mainstream health care systems. Suggestions for improving access to palliative care include building trust between homeless persons and health professionals, increasing collaboration between and flexibility within services, and providing more training and support for all professionals. Conclusions The provision of palliative care can be complicated for all populations, however delivering palliative care for people who are homeless is influenced by a potentially greater and more varied range of factors, on both individual and systemic levels, than providing palliative care for the housed population. Careful consideration and potentially great changes will be needed within health care systems to ensure homeless populations have equitable access to palliative care.